Phytochemical Test and Effectiveness of Alang-alang Stolon Extract (Imperata cylindrica L.) Against Mortality of Dengue Fever Mosquito Larvae (Aedes Sp.) - Ray Natalia Antou; Rudi Alexander Repi; Marthy Taulu (Indonesian Biodiversity Journal, 2022)
Aedes sp. is a species of mosquito that acts as a vector for transmitting dengue. The use of chemical insecticides to control Aedes sp. result in negative impacts on the environment. One vector control of dengue fever is using plant-derived insecticides, namely stolon Alang-Alang extract Imperata cylindrica L. which is known to be more effective against dengue fever mosquitoes Aedes sp. This study aims to determine the effectiveness of stolon alang-alang extract against the mortality of dengue mosquito larvae in Aedes sp. The method in this study is to analyze mortality data using Microsoft Excel 2016 probit analysis using seven treatments and three replications with a concentration of 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, and 0.5%. Larvae were tested at each concentration of as many as ten tails. The effectiveness of stolon alang-alang extract on larval mortality was observed every 12-72 hours. The data were analyzed by calculating the LC50 value using probit analysis. The results showed that alang-alang stolon extract effectively killed the mosquito larvae of Aedes sp. ranging from 0.25-0.5% concentration. The highest mortality rate was obtained at a concentration of 0.3-0.5%, capable of killing 100% of the mosquito larvae of Aedes sp. A concentration of 0.3-0.35% can cause 100% mortality of larvae at 60 hours after application (JSA), a concentration of 0.4% can cause 100% mortality in 48 (JSA) and a concentration of 0.45-0.5% causes 100% mortality of larvae in 36 (JSA). Probit analysis showed the LC50 result was 0.2116% (2115.5 ppm) with a toxic category (500-5000 ppm).